Critical literacy in the digital age: discourse analysis of online learning materials in Indonesian higher education - Fitriya Dessi Wulandari (Indonesian Journal of Linguistics and Educational Studies, 2026)
Background: The expansion of digital higher education in Indonesia has intensified the need to examine how critical literacy is constructed within online learning environments shaped by platform infrastructures and institutional governance. Objective: This study investigates how critical literacy is discursively framed, multimodally represented, and pedagogically enacted in online modules, video lectures, LMS discussions, and national MOOC platforms in Indonesian higher education. Method: Using a qualitative critical design integrating Critical Discourse Analysis (Fairclough), Multimodal Discourse Analysis (Kress & van Leeuwen), and Luke and Freebody’s Four Resources Model, the study analyzes 100 digital learning artifacts across public and private universities. Results: The findings indicate that critical literacy is predominantly framed as individualized cognitive competence rather than structural ideological critique. Multimodal design patterns replicate linear, print-based epistemologies despite digital affordances. Student engagement clusters at code-breaking and reflective levels, with limited ideological interrogation. Assessment rubrics privilege correctness and completion over transformative critique. Hyperlink ecologies and dialogic affordances remain underutilized. Implication: These findings imply that advancing critical literacy in digital higher education requires redesigning pedagogical, multimodal, and assessment practices to move beyond cognitive skills toward deeper ideological engagement and transformative digital citizenship. Novelty: The novelty of this research lies in its integrated multi-layered framework that connects discourse, multimodal design, and engagement analytics to reconceptualize online learning materials as ideological sites shaping semi-critical digital citizenship.